INTERVENSI PENCEGAHAN KESEPIAN LANSIA DI KELUARGA (SIAGA) BERBASIS ANDROID - Ezalina, Ezalina; Deswinda, Deswinda; Maputra, Yantri (Jurnal Kesehatan, 2025)
Loneliness is a significant threat to mental and physical health for older adults and an urgent problem of community’s health. It needs loneliness prevention application for older adults in family (SIAGA) based on android which appropriate to older adults needs. Objective: to know the effect of using SIAGA application toward loneliness prevention for older adults in family. Method: Quasi Experimental Research with pre test and post-test non equivalent control group approach. The sample includes 100 older adults who live with family. The sample was devided into two groups, namely 50 persons in experimental group which was given SIAGA application and 50 persons in control group which was not given SIAGA application. Sample was taken by using multistage clustered sampling from Payung Sekaki District in between June until July 2025. The data collection tools used questionnaires, including sociodemographic questionnaires and loneliness questionnaires (UCLA Loneliness Scale), which were administered directly to the older adults by the researchers. Intervention was done for 4 weeks. Data analysis consists of descriptive statistics, bivariat analysis used independent T-Test and multivariat analysis with General Lineal Model through repeated measurements (2 weeks and 4 weeks). Result: it shows the decreasing of loneliness of older adults in experimental group, namely before and after 2 weeks and 4 weeks of giving SIAGA application